Caracterização e seleção tecnológica de culturas lácticas isoladas de queijo de coalho do sertão alagoano - Ramos, Alécia Cristinne Santos (2009)
This project was developed aiming to establish physico-chemical, sensory and microbiological characteristics of coalho cheese (rennet coagulated cheese) prepared from raw Milk. Three processing plants were periodically visited in order to establish the coalho cheese preparation flow chart, and to collect samples for microbiological (coliforms at 35oC, thermotolerant coliforms, yeasts and molds, generic E. coli, Listeria monocytogenes, Staphylococcus aureus e Salmonella sp.), physico-chemical (pH, titratable acidity, fat, ashes, moisture, total protein and chlorides) and sensorial (appearance, odor, texture / mouth feel and taste). Lactic bacteria (LAB) were also isolated and identified as the major component of the microflora. Their technological properties were evaluated in order to develop an starter culture that could be used to produce coalho cheese from pasteurized milk, with the same characteristics of the raw milk cheese. Sensorial analysis indicated that the cheeses from the three plants had different characteristics, probably derived from the different processing conditions observed during salting, pasteurization and heating of the curd. Physico-chemical analysis showed that the cheeses have medium to high moisture content and low fat. The sanitary and hygienic conditions of the final product were considered inadequate considering E. coli and S. aureus countings, although no Salmonella or L. monocytogenes were detected. Amongst the LAB isolates (109) the following genera could be identified: Streptococcus (41,9%), Enterococcus (16,3%), Pediococcus (9,3%), Leuconostoc (9,3%), Lactobacillus (4,6%) and Lactococcus (2,3%). The major species identified were: Streptococcus vestibularis, Streptococcus mutans, Streptococcus uberis, Streptococcus bovis, Lactobacillus plantarum, Lactobacillus paracasei ssp. paracasei, Pediococcus pentosaceus e Lactococcus lactis. Twenty four of the LAB isolates were fast acid producers indicating their usefulness as starter culture. Other technologically relevant properties observed among these 24 strains were proteolitic capacity and flavor producing. Properties. However, additional studies are necessary to evaluate these cultures in the processing of the coalho chesse from pasteurized milk, as well as the virulence of the Streptococcus strains isolated.